A study of select open access journals and their business models listed in DOAJ in the fields of civil and structural engineering - Poorna, R. Lakshmi; Mymoon, M.; Hariharan, A. (Journal of Structural Engineering, 2024)
Open access (OA) refers to unrestricted online access to articles published in scholarly journals, and also increasingly to book chapters or monographs. The distribution is mainly achieved through world wide web and allows the users to read, download, copy, distribute, print, search, or link to the full texts of these articles without any subscription or access fee. This paper aims to provide an oversight on the different OA categories and also describes a comprehensive study undertaken on the direct OA journals and its business models as listed in the Directory of Open Access Journals (DOAJ) in the fields of civil engineering, structural engineering and related areas. Sixty nine journals in English language have been taken for this study where in articles in the areas of CSIR-SERC’s research interests are published. From this study, we found that almost two thirds of these open access journals do not charge article processing fee and there are many options for researchers/scientists to explore, with respect to publishing in open access journals.